Sapere Aude – Dare to be Wise: Karen D. Liller - Karen Liller (Health Behavior Research)
Sapere Aude – Dare to Be Wise is a unique editorial conversational interview-type feature. It is an attempt to deep dive into an Academy members’ background, formative experience, and education – specifically, to extract factors that contributed to their development and evolution as a professional, as well as their success as a prominent researcher in the health behavior arena. Every Academy member selected has a different story to tell and numerous models for success will emerge from this exploration of the membership.